The dialogue between the judge and the teacher - Ghersi, Enrique (2007)
This article, through a dialogue between a professor and a judge, tries to describe with a language quite easy to understand, the crime of illicit usurpation and the principle of agreement, which when inverted causes the land invasions to become a way of original acquisition of the property in some cases. In addition, it comments the relation between the law and the custom, being both sources of rights that coexist in the society.